The Relationship between Nutrition in Infancy and Cognitive Performance during Adolescence - Nyaradi, Anett; Oddy, Wendy H.; Hickling, Siobhan; Li, Jianghong; Foster, Jonathan K. (Frontiers in Nutrition, 2015)
Objectives: In this study, we aimed to investigate the long term associations between breastfeeding duration during infancy, diet quality as measured by a diet score at one year of age and cognitive performance during adolescence. Methods: Participants (n= 717) were recruited from the West Australian Pregnancy Cohort (Raine) Study, a prospective longitudinal study of 2868 children and their families based in Perth, Western Australia. Breastfeeding duration and an early diet score at age one year were used as the main predictor variables, while a computerized cognitive battery (CogState) was used to assess adolescents’ cognitive performance at 17 years. The diet score, which has seven food group components, was based on a 24-hour recall questionnaire completed by the mother at one year of age. A higher diet score represents a better, more nutritious eating pattern. Associations between breastfeeding duration, diet score and cognitive performance were assessed in multivariable regression models. Results: Higher diet scores at one year representing better diet quality were significantly associated with faster reaction times in cognitive performance at 17 years (Detection Task: β= -0.004, 95% CI: -0.008; 0.000, p= 0.036; Identification Task: β= -0.004, 95% CI: -0.008; 0.000, p= 0.027). Breastfeeding duration (≥ 4 months) was also significantly associated with a shorter reaction time, but only for males (Detection Task: β= -0.026, 95% CI: -0.046; -0.006, p= 0.010). Conclusion: Nutrition in early childhood may have a long term association with fundamental cognitive processing speed, which is likely to be related to enhanced brain development in the first year of life.